2002
DOI: 10.1115/1.1445148
|View full text |Cite
|
Sign up to set email alerts
|

Error Model and Accuracy Analysis of a Six-DOF Stewart Platform

Abstract: Precision machining operations necessitate highly accurate, rigid, and stable machine-tool structures. In response to this need, parallel architecture machines, based on the concepts of the Stewart Platform, are emerging. In this paper, considering major inaccuracy factors related to the manufacture, geometry, and kinematics, of such machines, first and second order error models are presented, and followed by a comparative assessment of these models in conjunction with illustrative examples. Furthermore, in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…The studies by Sandia National Laboratories [3] and the National Institute of Standard and Technology [4] reported that two commercially scaled hexapod prototypes have the horizontal stiffness of 7 ∼ 46 N/µm and 32-71 N/µm varied in the working zone. Another work [5] also stated that a commercially scaled hexapod There is an extensive body of literature [6][7][8][9][10][11][12][13][14][15][16][17][18] devoted to the characterisation, calibration and compensation for the error sources in PKMs, using either external devices for direct calibration or internal sensors for self-calibration. However, implementing these methods in a machine shop environment is a challenging task for machine builders.…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Sandia National Laboratories [3] and the National Institute of Standard and Technology [4] reported that two commercially scaled hexapod prototypes have the horizontal stiffness of 7 ∼ 46 N/µm and 32-71 N/µm varied in the working zone. Another work [5] also stated that a commercially scaled hexapod There is an extensive body of literature [6][7][8][9][10][11][12][13][14][15][16][17][18] devoted to the characterisation, calibration and compensation for the error sources in PKMs, using either external devices for direct calibration or internal sensors for self-calibration. However, implementing these methods in a machine shop environment is a challenging task for machine builders.…”
Section: Introductionmentioning
confidence: 99%
“…Because of unpredictable environment some hexapod elements may have values different from nominal. This can be due to the assembly errors, elastic and thermal deformations, actuator errors and others error sources (Wang, 1995). Model that includes all sources of errors is hardly possible to implement because of nonlinear dependent error sources and most of error elements can't even be calculated or measured.…”
Section: Error Analysismentioning
confidence: 99%
“…Considering all error sources such as the bar length errors, the ball joints and Hooke joints installation errors of 3-UPS-PU parallel mechanism, we use differential transformation method to solve position and orientation error of end-effector [7].…”
Section: Error Modeling Of the Parallel Mechanismmentioning
confidence: 99%